1954
DOI: 10.1039/df9541800135
|View full text |Cite
|
Sign up to set email alerts
|

Flocculation of kaolinite due to the attraction of oppositely charged crystal faces

Abstract: Pure kaolinite washed first with 1 M NaCl containing 0.001 M HCI and then with distilled water remains firmly flocculated when salt free. In this state the kaolinite retains exchangeable Na, which shows that the crystals are negatively charged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
138
0
2

Year Published

1959
1959
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(147 citation statements)
references
References 0 publications
7
138
0
2
Order By: Relevance
“…Two of the samples studied did contain montmorillonite, and these had exchange capacities of 5 and 7 ; therefore they were not included on the plot of exchange capacity and degree of crystallinity is one that would be expected because if the kaolins were disordered in the stacking, then there would be more exposed charged sites for exchange to take place. Schofield and Samson (1955) and others recently have indicated that exchange is due to substitution within the lattice, and that broken bonds are a relatively minor cause of base exchange. Another property that was correlated with degree of crystallinity was surface area, measured by the BET method in square meters per gram.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the samples studied did contain montmorillonite, and these had exchange capacities of 5 and 7 ; therefore they were not included on the plot of exchange capacity and degree of crystallinity is one that would be expected because if the kaolins were disordered in the stacking, then there would be more exposed charged sites for exchange to take place. Schofield and Samson (1955) and others recently have indicated that exchange is due to substitution within the lattice, and that broken bonds are a relatively minor cause of base exchange. Another property that was correlated with degree of crystallinity was surface area, measured by the BET method in square meters per gram.…”
Section: Discussionmentioning
confidence: 99%
“…A kaolinite edge develops a positive charge on the acceptance of a proton by the edge hydroxyl group from the solvent (Schofield and Samson, 1954). The reaction may be represented as:…”
Section: Forces Controlling Sediment Volumementioning
confidence: 99%
“…A study of the behavior of kaolinite in suspension has shown that pure Na-kaolinite flocculated at pH < 7 under conditions that dispersed illite and montmorillonite (Schofield and Samson, 1954). The acidified kaolinite retained exchangeable Na, indicating that the clay crystals were negatively charged.…”
Section: Introductionmentioning
confidence: 99%
“…At pH 8, CIwas desorbed from the crystals indicating that the edges were no longer positively charged. Hence, eliminating the positive charges at the edges of the kaolinitic clay plates, dispersed the clay (Schofield and Samson, 1954).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation